(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Pleomorphic adenoma is the most common benign tumor of the salivary glands, characterized by high histological and morphological heterogeneity. This article examines the macroscopic and microscopic features of this neoplasm, its cellular composition, growth patterns, as well as histochemical and immunohistochemical characteristics. Special attention is given to the localization of the tumor in the parotid, submandibular, and minor salivary glands, which determine its clinical course and treatment strategy. Understanding the morphological features of pleomorphic adenoma plays a key role in its timely diagnosis and the selection of the optimal surgical approach.